2016
DOI: 10.2169/internalmedicine.55.6222
|View full text |Cite
|
Sign up to set email alerts
|

Limbic Encephalitis Associated with Sjögren's Syndrome: Report of Three Cases

Abstract: Sjögren's syndrome (SS) may be complicated by neurological manifestations. We herein report three women (age range 26-60 years old) who all presented with limbic encephalitis (LE) as the predominant clinical feature 3 months to 15 years after the diagnosis of SS. The 26-year-old patient also developed acute motor axonal neuropathy one week after autoimmune encephalitis. All three patients showed contrast-enhanced MRI lesions and inflammatory cerebrospinal fluid findings, while not displaying any anti-neuronal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Furthermore, as anti-Ro/SSA antibodies were identified in the CSF of the patients with SjS with cerebellar degeneration, it is possible that these antibodies might attack Purkinje cells, reducing Purkinje cell functions and activities, and can cause symptoms of neurological degeneration, resulting in cerebellar atrophy. Several reports have shown the presence of serum anti-Ro/SSA antibodies in patients with SjS with limbic encephalitis [11,29]. We demonstrated that Ro52/TRIM21 was expressed in the neurons of the cortex and hippocampus, which might indicate that anti-Ro/SSA antibodies are involved in other CNS diseases in addition to cerebellar degeneration.…”
Section: Discussionmentioning
confidence: 50%
“…Furthermore, as anti-Ro/SSA antibodies were identified in the CSF of the patients with SjS with cerebellar degeneration, it is possible that these antibodies might attack Purkinje cells, reducing Purkinje cell functions and activities, and can cause symptoms of neurological degeneration, resulting in cerebellar atrophy. Several reports have shown the presence of serum anti-Ro/SSA antibodies in patients with SjS with limbic encephalitis [11,29]. We demonstrated that Ro52/TRIM21 was expressed in the neurons of the cortex and hippocampus, which might indicate that anti-Ro/SSA antibodies are involved in other CNS diseases in addition to cerebellar degeneration.…”
Section: Discussionmentioning
confidence: 50%
“…Furthermore, since anti-Ro/SSA antibodies were identi ed in the CSF of the SjS patients with cerebellar degeneration, it is possible that the anti-Ro/SSA antibodies might attack Purkinje cells, reducing Purkinje cell functions and activities, and cause symptoms of neurologic degeneration, resulting in cerebellar atrophy. Several reports have shown the presence of serum anti-Ro/SSA autoantibodies in SjS patients with limbic encephalitis [9,29]. We demonstrated that Ro52/TRIM21 was expressed in the neurons of the cortex and hippocampus, which might indicate that anti-Ro/SSA autoantibodies are involved in other CNS involvements in addition to cerebellar degeneration.…”
Section: Discussionsupporting
confidence: 49%
“…Previous studies on seronegative LE included isolated case reports with incomplete immunological studies, e.g. published before the description of antibodies closely associated with LE such as GABA B R antibodies, LE associated with systemic autoimmune disorders or LE resulting from immunological adverse effects of immune check‐point inhibitors .…”
Section: Discussionmentioning
confidence: 99%